Architectural connections between western Central Asia and China: new investigations at Haermodun (cal AD 90–321), a fortified circular settlement in Xinjiang, China. (April 2021) - Li, Yuqi; Storozum, Michael; Li, Haiming; Hu, Di; Wang, Xin; Jia, Xin
Abstract: Abstract : The architectural connections between western Central Asia and China are not well understood. Recent investigations at the Haermodun site in central Xinjiang reveals new evidence of the influence of western Central Asia on the construction of fortifications in China during the early first millennium AD.